When New Zealend was Attacked: The Failure of The UN'S Global Counter-Terrorism Strategy? - Benarrivo, Renaldo (UIN ALAUDDIN MAKASSAR, 2025)
The spectrum of security threats continues to grow. This occurs due to broadening the meaning of security from traditional to non-traditional. The consequence of this phenomenon is that no country is truly safe because threats come that are difficult to predict. For example, the threat of terrorism, an attack that is not always institutionalized and often takes the form of individual actions, makes it challenging to overcome without a unique strategy. As a country that is known to be safe, New Zealand is not immune from the threat of terrorism. Even though the UN already has a Global Counter-Terrorism Strategy, it has little impact, especially when talking about the Christchurch tragedy, which has attracted world attention. From a national security perspective, the research describes how the United Nations Global Counter-Terrorism Strategy (UNGCTS) should be operationalized and why countries like New Zealand could miss out. Using a qualitative approach as a research method, at the end of this research, it was concluded that many factors must be considered when discussing countering terrorism, not just relying on general norms or rules and forgetting about micro-managing efforts.